A control theoretic approach to the treatment of AIDS - De Souza, José A. M. Felippe; Caetano, Marco Antonio Leonel [UNESP]; Yoneyama, Takashi (Institute of Electrical and Electronics Engineers (IEEE), 2001)
This work concerns the problem of optimizing the drug doses in the treatment of AIDS by looking for a balance between the therapeutic response and the side effects. Extensive computer simulation and comparison with the constant dose scheme evaluate the results. For some few cases the results are also compared with actual clinical data. A mathematical model describing the dynamics of HIV virus and CD4 cells is initially fitted to actual published clinical data. The identified model is then used to compute the sub-optimal drug doses for the treatment of AIDS by a direct method of optimization using a performance index of Bolza type. The sub-optimal treatment scheme is shown to achieve a therapeutic response close to the constant dose strategy, but with lower cost, as measured by the proposed performance index.
Keywords: farmacotherapy; Optimal control; optimization; simulation; viral infections